Bacterial Species and Antibiotic Resistance-A Retrospective Analysis of Bacterial Cultures in a Pediatric Hospital - Bianca Prajescu; Liana Gavriliu; Mara Ioana Iesanu; Andreea Ioan; Anca Andreea Boboc; Catalin Boboc; Felicia Galos (MDPI AG, 2023)
Antimicrobial resistance (AMR) has become a major healthcare concern having a rising incidence, especially in pediatric patients who are more susceptible to infections. The aim of our study was to analyze the bacterial species isolated from patients admitted to our tertiary hospital and their AMR profiles. We conducted a retrospective observational study by examining the bacterial cultures collected from pediatric patients admitted to our hospital over a period of one year. We identified the most common bacterial species from 1445 clinical isolates and their AMR patterns using standard microbiological techniques. Our analysis revealed that the most frequently isolated bacterial species were Escherichia coli (23.73%), Staphylococcus aureus (15.64%), Klebsiella species (12.04%), and Pseudomonas species (9.96%). Additionally, these species exhibited varying levels of resistance to commonly used antibiotics. Notably, we observed high rates of resistance among Gram-negative bacteria, including extended-spectrum beta-lactamase-producing Escherichia coli and Klebsiella species. Among Gram-positive bacteria, we observed a high level of methicillin-resistant Staphylococcus aureus. Our findings highlight the urgent need for effective antibiotic management programs and infection control measures to address the rising incidence of AMR in pediatric hospitals. Further research is needed to identify the mechanisms of resistance in these bacterial species and to develop new strategies for preventing and treating infections caused by antibiotic-resistant bacteria in pediatric patients.